Folded crossed-dipole antenna for circular polarization - Kedze, Kam Eucharist; Park, Ikmo (2020 International Workshop on Antenna Technology, iWAT 2020, 2020)
We present a small compact crossed-dipole antenna comprising two printed folded crossed-dipole arms and a pair of vacant quarter printed rings to generate circular polarization (CP). The design of a compact, small-sized CP antenna is realized by rotating the arms of a conventional crossed dipole and then folding the rotated arms twice into a figure-eight-like structure. By undertaking these rotation and folding techniques, we achieve a miniaturized CP crosseddipole antenna that performs satisfactorily. The compact crossed-dipole folded antenna with overall dimensions of 22.3 mm×39.9 mm×0.508 mm (0.22 λ0 × 0.39 λ0 × 0.0052 λ0 at 3.07. GHz) has a measured S11| <-10 dB impedance bandwidth of 2.81-3.51 GHz (22.15%) and a simulated 3-dB axial bandwidth of 2.85-3.30 GHz (14.63%).
Keywords: Crossed dipoles; Crossed-dipole antenna; Folded antennas; Folding technique; Impedance bandwidths; Antenna miniaturization; Broadband; Circular polarization; Crossed-dipole